The failure of political Islam - Roy, Olivier, 1949-; Harvard University Press (Cambridge, Mass. : Harvard University Press, 1994)
For many Westerners, ours seems to be the era of the "Islamic threat," with radical Muslims everywhere on the rise and on the march, remaking societies and altering the landscape of contemporary politics. In a powerful corrective to this view, the French political philosopher Olivier Roy presents an entirely different verdict: political Islam is a failure. Even if Islamic fundamentalists take power in countries like Algeria, they will be unable to reshape economics and politics and, in the name of "Islamic universalism," will express no more than nationalism or an even narrower agenda. Despite all the rhetoric about an "Islamic way," an "Islamic economy," and an "Islamic state," the realities of the Muslim world remain essentially unchanged.
Roy demonstrates that the Islamism of today is still the Third Worldism of the 1960s: populist politics and mixed economies of laissez-faire for the rich and subsidies for the poor. In Roy's striking formulation, those marching today beneath Islam's green banners are the same as the "reds" of yesterday, with similarly dim prospects of success. Roy has much to say about the sociology of radical Islam, about the set of ideas and assumptions at its core. He explains lucidly why Iran, for all the sound and fury of its revolution, has been unable to launch "sister republics" beyond its borders, and why the dream of establishing Islam as a "third force" in international relations remains a futile one. Richly informed, powerfully argued, and clearly written, this is a book that no one trying to understand Islamic fundamentalism can afford to overlook.
1. Islam and Politics: From Tradition to Reformism -- 2. The Concepts of Islamism -- 3. The Sociology of Islamism -- 4. The Impasses of Islamist Ideology -- 5. Neofundamentalism: From the Muslim Brotherhood to the Algerian FIS -- 6. The Islamist New Intellectuals -- 7. The Geostrategy of Islamism: States and Networks -- 8. The Islamic Economy: Between Illusions and Rhetoric -- 9. Afghanistan: Jihad and Traditional Society -- 10. Iran: Shiism and Revolution -- 11. The Shiite Factor in Iran's Foreign Policy -- Conclusion: Tomorrow's Gray Areas.
Includes bibliographical references (pages 225-229) and index.
Keywords: Islam and politics -- Middle East; Islam and politics -- Africa, North; Middle East -- Politics and government -- 1979-; Africa, North -- Politics and government